(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the need for scientific literature and networks of cyberattacks in recent decades to regulate computer communication, social control in cyberattacks, their capabilities and boundaries. Computerization is a new type of communication carried out using information technologies, created in the 70s of the last century as the fourth information revolution, which radically changed the ability of the media to influence culture, consciousness and human behavior. Also, from a sociological point of view, it was studied that in recent years the process of institutionalization of this new type of human activity has intensified - the production, storage and transmission of information using information technologies.